DIFFERENCES IN METAMORPHOSIS OF HONEY BEES Apis mellifera IN ROMANG ISLAND - Mayaut, Gratia; Nindatu, Maria; de Kock, Rahel Hendrijete (Universitas Pattimura, 2020)
Honey bees (Apis mellifera) on Romang Island are scattered at several different points with abundant populations. The research location was carried out at two points, namely the first location is near residential areas, the height above sea level is approximately 10 meters, tends to be more crowded while the second location is far from settlements, the height above sea level is approximately 350 meters. The variables measured were the different metamorphosis phases of egg, larva, pupa, adult; temperature, food sources such as flowering plants, forest plants or fruit trees around the site. The difference in the time of metamorphosis of honey bees in the first location, seven days for laying eggs, five days for larvae, nine days for pupae, and seven days for adults while in the second location is six days for eggs, five days for larvae, ten days for pupae, and three days for adults. So the metamorphosis of honey bees in a quiet location and away from settlements shows a shorter duration compared to locations near settlements.